Effect of weaning age on growth measurements and sero-biochemical parameters in Murrah buffalo calves - BHARTI, P K; DUTT, TRIVENI; PATEL, B H M; PANDEY, HARI OM; OJHA, BRIJESH; KAMAL, REENA; UPADHYAY, DEEPAK; SINGH, MUKESH; GAUR, G K (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to compare the effect of weaning at different ages on growth measurement traits and serum biochemical parameters in Murrah buffalo calves from birth to 90 days of age. Out of 42 buffalo calves, 35 were randomly assigned in to 3 groups, viz. control (C): suckling (14); treatment T1 (T1): weaning of calves at birth (11); and treatment T2 (T2): weaning of calves at 45th day of birth (10). The mean body weight gain was significantly higher in control followed by T2 and T1. The mean initial body length of calves in control, T1 and T2 were 59.35±0.58, 56.64±0.99 and 57.20±0.91 cm, respectively. The final body length (cm) was significantly higher in control than T1 and T2. Similar trends were observed for height at wither and heart girths of calves in different groups though there were initial differences as well. The serum cortisol (nM/l) was significantly higher only at day-60th of sampling in T2 followed by T1 and control. The serum glutamic pyruvic transaminase (SGPT) was significantly higher at 45th and 60th days of sampling in T1 and T2 than control group. The weaned groups of calves had comparatively lower growth values than suckling, however, the significant differences on serum biochemical parameters were observed only at few stages of weaned buffalo calves as compared to suckling group, which indicates minor inconsistent physiological deviations. The weaning in buffalo calves at early stages affects body growth parameters with minor inconsistent changes in blood biochemical profile.